2023
DOI: 10.3390/biom13020306
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Ovarian Cancer Prognostic Model Based on the Investigation of Ferroptosis-Related lncRNA

Abstract: (1) Background: Ovarian cancer (OV) has the high mortality rate among gynecological cancers worldwide. Inefficient early diagnosis and prognostic prediction of OV leads to poor survival in most patients. OV is associated with ferroptosis, an iron-dependent form of cell death. Ferroptosis, believed to be regulated by long non-coding RNAs (lncRNAs), may have potential applications in anti-cancer treatments. In this study, we aimed to identify ferroptosis-related lncRNA signatures and develop a novel model for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Remarkably, this signature with only two genes demonstrated good predictive power as revealed by the ROC curve (Figure 4). Its predictive capability, estimated by the AUC value of ROC curve, is comparable with that of most OV prognostic signatures consisting of more genes, i.e., an aging-related gene signature with 8 genes [39] and is even better than a signature of ferroptosis-related long noncoding RNAs (lncRNAs) with 18 lncRNAs [40]. In addition, univariate and multivariate Cox regression analyses identified both age and risk score as independent prognostic factors for OV patients.…”
Section: Advances Of the Ubrgs Signature For Prognostic Prediction In Ovmentioning
confidence: 83%
“…Remarkably, this signature with only two genes demonstrated good predictive power as revealed by the ROC curve (Figure 4). Its predictive capability, estimated by the AUC value of ROC curve, is comparable with that of most OV prognostic signatures consisting of more genes, i.e., an aging-related gene signature with 8 genes [39] and is even better than a signature of ferroptosis-related long noncoding RNAs (lncRNAs) with 18 lncRNAs [40]. In addition, univariate and multivariate Cox regression analyses identified both age and risk score as independent prognostic factors for OV patients.…”
Section: Advances Of the Ubrgs Signature For Prognostic Prediction In Ovmentioning
confidence: 83%
“…Patients characterized by higher RS demonstrated heightened sensitivity to immunotherapeutic interventions, suggesting that TAMGs may serve as prospective predictive biomarkers for the assessment of immunotherapeutic outcomes. While prognostic models in the context of OC have received considerable research attention, the development of predictive models for characterizing TAMs in OC remains a notably unresolved aspect [41][42][43][44]. This article offers a valuable source of information that can potentially enhance the understanding of TAMs in OC and provide a foundation for further study in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [55] have identi ed a signature that includes 18 Ferroptosis-Related lncRNAs and constructed a risk-scoring model and the KM survival analysis indicated that there was a signi cant difference (p < 0.0001) in survival rates between the high-and low-risk groups.Perhaps in the future, GPCRRGs and non-coding genes can be combined to predict the prognosis of ovarian cancer might have a higher predictive value.The RGS17, RGS16, RGS1 and RGS8 of the RGS (regulator of G protein signaling) gene family have been screened and identi ed as diagnostic biomarkers for the immunologic subtypes of ovarian cancer [56].…”
Section: Discussionmentioning
confidence: 99%